The mechanism of NF-κB-TERT feedback regulation of granulosa cell apoptosis in PCOS rats. - Haoxuan Xue; Zecheng Hu; Shun Liu; Shun Zhang; Wenqin Yang; Jiasi Li; Chulin Yan; Jiaming Zhang; Jing Zhang; Xiaocan Lei (PLoS ONE)
Patients with Polycystic ovary syndrome (PCOS) have chronic low-grade ovarian inflammation. Inflammation can cause telomere dysfunction, and telomere and telomerase complex are also involved in regulating inflammation. However, the specific mechanisms of inflammatory signaling feedback and telomere-telomerase mutual regulation remain to be discovered. This study elucidates the role of Nuclear factor kappa-B (NF-κB)-Telomerase reverse transcriptase (TERT) feedback in PCOS granulosa cell apoptosis. Using letrozole and a high-fat diet, a PCOS rat model was established, along with a Lipopolysaccharide (LPS) -treated KGN cell inflammation model was established. NF-κB and TERT inhibitors (BAY 11-7082 and BIBR1532) were then administered to LPS-induced KGN cells. PCOS rats displayed disrupted estrous cycles, increased weight, elevated serum testosterone, cystic follicles, granulosa cell layer thinning, and reduced corpora lutea count (P are all less than 0.05). In PCOS rat ovaries, NF-κB, Interleukin-6 (IL-6), Tumor Necrosis Factor α (TNF-α), TERT, Bax, and Caspase-3 exhibited notable upregulation, while Bcl-2 decreased, with telomere elongation (P are all less than 0.05). There were significant correlations among NF-κB-related inflammatory factors, TERT and apoptotic factors, and they were positively correlated with Bax and Caspase-3, and negatively correlated with Bcl-2 (P are all less than 0.05). LPS-treated KGN cells demonstrated increased expression of inflammatory and pro-apoptotic factors, later restored post-treatment with NF-κB and TERT inhibitors (P are all less than 0.05). In conclusion, TERT may induce granulosa cell apoptosis by participating in the regulation of the NF-κB signaling pathway, thereby mediating the chronic inflammatory response of PCOS through downstream inflammatory factors IL-6 and TNF-α.